Segmental flexibility and complement fixation of genetically engineered chimeric human, rabbit and mouse antibodies. - Dangl, J L (1988)
We generated a family of chimeric immunoglobulin G (IgG) molecules having identical antigen-combining sites for the dansyl (DNS) hapten, in conjunction with nine heavy chain constant (CH) regions. This family of antibody molecules allows comparison of CH dependent properties independent of possible variable region contributions to IgG function. The segmental flexibility and complement fixation activity were measured of six genetically engineered molecules (the four human IgG isotypes, mouse IgG3 and rabbit IgG) and the remaining three mouse IgG isotypes, (IgG1, IgG2a and IgG2b), isolated previously by somatic cell genetic techniques. These properties of antibody molecules each correlate with the length of the immunoglobulin hinge region which separate the first and second CH (CH1 and CH2) domains. These results attribute a structural basis for two critical properties of antibody molecules.